Influências de processos hidrológicos no desempenho de um wetland construído de fluxo vertical de fundo saturado - Santos, Kelly Silva dos (2022)
Hydrological processes that occur in constructed wetland study systems (CWs) are considered difficult to determine and, consequently, there are few on the subject. Evapotranspiration and different local variables in CWs as local and fluent conditions vary significantly in local and fluent variables in weather systems since as applications local variables are not affected by the treatment. This study aimed to evaluate the interception of rain and evapotranspiration and their influence on the treatment efficiency of a vertical flow constructed wetland from saturated bottom (VSFCW), with 0.30 m of saturation, a surface area of 24.5 m² and with Canna x generalis. The macrophyte was monitored during its development in two different cycles (C1 and C2) with the system operating with a HLR of 54.1 mm.d-¹ and 33.7 mm.d-¹ along the C1 and C2, respectively. Canna x generalis. Good adaptation and rapid growth, providing high rates of evapotranspiration and interception in both cycles. The development of the non-C2 macrophyte was slower, although it may be less than the increase in slowness (P). In C1, the leaf area (Al) and the leaf area index (LAI) of Canna x generalis reached 5393 cm² and 41 m².m-², while in C2 they were 3075 cm² and 21.25 m².m-². The good development of vegetation in C1 corroborated to a total interception (I) of 79.6% of P, internal precipitation (Pi) of 18.9% of P and trunk runoff (Et) of 1.7% of P. For C2, the total of I was 61.5% of P, Pi of 35.5% of P and Et of 2.92% of P. Regarding the loss of water, the two cycles resulted in an evapotranspiration reference (ET0) average (obtained by the Penman-Monteith equation) of 3.94 mm.d-¹, determined from local meteorological data. Crop evapotranspiration (ETc) determined by an inlet and outlet water balance (74% higher than climatic conditions ETc) was approximately 74% higher than climatic conditions, resulting in approximately 84 mm.d-¹. In total, a net loss attributed to ETc was 27% of the volume entering the VSFCW. The evaporation measured on site by the class A tank (TCA) was mostly higher than ET0. Based on this monitoring, the crop (Kc) and TCA (Kt) coefficients were determined. The average Kc was observed at 1.98 and 1.81 for C1 and C2, respectively, with a maximum value of Kc in December/20 and early January/21, a period predicted by the advanced development phase of the next one. The mean Kt was 1.53 and 1.2 for C1 and C2, respectively. The inspiration strength of rainy days and days with water loss by evapotranspiration average COD removal efficiencies of 83% on dry days, due to evapotranspiration, and after 87% on days of evapotranspiration, due to organic load dilution events.